Chronicles of a radical hag (with recipes) : a novel - Landvik, Lorna, 1954- (University of Minnesota Press, 2019)
"In the small town of Granite Creek, Minnesota, Haze Evans suffers a stroke at the age of 89 and slips into a coma. Haze is a local legend, having written a daily column in the Granite Creek Gazette for fifty years running"--